Education and systematization of nursing care for psychosocial care (Research, Society and Development, 2020)
This article aims to present an integrative literature review conducted in August 2019, on the bases PubMed, LILACS, BDENF, ERIC, Scielo including articles available in full, published between the years 2015 to 2019. To identify the use of permanent health education in the construction and application of the systematization of nursing care in psychosocial care centers. 482 articles were found, 05 articles were selected that deal with the theme of the study and fit the inclusion criteria. After reading and analyzing, two categories emerged: Permanent Education in Health to elaborate / build care in Mental Health and Permanent Education in Health to promote reflection / professional knowledge. Despite the high number of occurrences of articles in the various databases dealing with the themes of Mental Health, Systematization of nursing care and permanent education, Permanent Education in Health was not found as a process for the elaboration, implementation or maintenance of Systematization of Health Care Mental Health Nursing, but as a space for discussion and reflection of professional identity, empowerment of psychiatric nursing and qualification of nursing care provided in mental health. None of the articles dealt with community health services or another substitute device in psychosocial care.